Male Osteoporosis - Meltem Esenyel (Türk Osteoporoz Dergisi, 2004)
Osteoporosis in men is now recognized as an increasingly important public health issue. About 30 % of hip fractures and 20 % of vertebral fractures occur in men. In the present study, we examined 19 men who did not have major risk factors that might affect bone mass. Parathormone(PTH), osteocalcin (marker of bone formation, OC) and deoxypyridinoline (marker of bone resorption, DPD) were measured. The bone mineral density (BMD) measurements in 16 men were performed by dual-energy X-ray absorbtiometry (DXA) from lumbar spine (L2-4), and left hip. Bone density at each site was categorized as osteoporosis or osteopenia according to World Health Organization (WHO) criteria. In 19 patients with a mean age of 69 years, PTH levels were in the normal range except one patient. OC levels were elevated in %42.1 and DPD levels were elevated in 74 % of patients. L2-4 T score was osteoporotic (25%) in 4 patients and osteopenic (25%) in 4 patients. Femur Ward’s T score was osteoporotic (37.5%) in 7 patients and osteopenic (37.5%) in 7 patients. Osteoporosis is a significant problem in older men. Increased awareness for the risk factors of male osteoporosis is an important issue. Early diagnosis and treatment would help to reduce morbidity and mortality resulting from osteoporotic fractures.